FAKTOR â€“ FAKTOR YANG MEMPENGARUHI PERMINTAAN LOGAM MULIA PADA PT. PEGADAIAN CABANG PONTIANAK - DEWANTI B01109044, THEODESIA IKA RORO (Jurnal Curvanomic, 2015)
The study of this research is â€œThe factors of demand noble metal in PT. Pegadaian Pontianak.â€ The Purposes of this research is knowing and analyzes the factors of demanding noble metal PT. Pegadaian Pontianak. The analysis of methode of this research is qualitative descriptive methode. The Resources used by primary data and secondary data. Samples of this research are about 35 respondent. The conclusion of this research is the primary demanding to respondent of noble metal in PT Pegadaian Pontianak. To Investigate the other supporter factors is price, income, promotion, service, and subtitusi goods.